2010
DOI: 10.1007/s10853-010-4719-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving interfacial properties of a laser beam welded dissimilar joint of aluminium AA6056 and titanium Ti6Al4V for aeronautical applications

Abstract: of the original manuscript:Vaidya, W.V.; Horstmann, M.; Ventzke, V.; Petrovski, B.; Kocak, M.; Kocik, R.; Tempus, G.: AbstractDissimilar welds of aluminium alloy AA6056 and titanium alloy Ti6Al4V were produced by a novel technique. AA6056 sheet was machined at one end to a U-slot shape, enabling the intake of the Ti6Al4V sheet. The Al-alloy U-slot was then butt welded by split laser beam without using a filling wire, thus making a weld by melting only the Al-alloy.Thereby the intermetallic brittle phase TiAl 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…The reaction layer can be seen with non-uniform thickness along the transverse section. In previous works 1,8 , this reaction layer has been characterized as zones with club-shaped and cellular/ serration-shaped morphologies.…”
Section: Metallographic Characteristics Of the Dissimilar Jointsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction layer can be seen with non-uniform thickness along the transverse section. In previous works 1,8 , this reaction layer has been characterized as zones with club-shaped and cellular/ serration-shaped morphologies.…”
Section: Metallographic Characteristics Of the Dissimilar Jointsmentioning
confidence: 99%
“…The industrial demand for hybrid components has increased the necessity for joining dissimilar metallic materials 1,2 . Different techniques have been used for joining of dissimilar metals such as diffusion welding, brazing, friction stir welding, electron beam welding, and laser welding 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaidya et al [4] have shown in the frame of a feasibility study that the laser beam welding of Ti-6Al-4V and AA 6056 can be performed without any formation of cracks and pores, respectively. Chemical components, crystal structure, and melting points can be given as examples.…”
Section: Introductionmentioning
confidence: 99%
“…More complex geometrical configurations were also tested. For instance, Vaidya et al (2010) have also considered a butt-brazing condition, but with specifically designed u-shape AA 6056 samples, and a split-beam laser brazing to ensure a symmetrical contact with Ti6Al4V sheets. Last, Chen et al (2009) have investigated the effect of a rectangular laser spot on the dissimilar assembly of Ti6Al4V to 5A06 with V-shape groove and Al12Si eutectic filler wire.…”
Section: Introductionmentioning
confidence: 99%